2021
DOI: 10.3390/healthcare9040420
|View full text |Cite
|
Sign up to set email alerts
|

Online Problem-Based Learning in Clinical Dental Education: Students’ Self-Perception and Motivation

Abstract: The physical closure of higher education institutions due to coronavirus disease 2019 (COVID-19) shed a brighter light on the need to analyze, explore, and implement strategies that allow the development of clinical skills in a distance learning situation. This cross-sectional study aims to assess dental students’ self-perception, motivation, organization, acquired clinical skills, and knowledge using the online problem-based learning method, through the application of a 41-item questionnaire to 118 senior stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
0
19
0
6
Order By: Relevance
“…eLearning has been the medium of delivery of medical educational institutions to address the scarcity of medical professionals [ 30 , 31 , 32 ]. In this study, the Unified Theory of Acceptance and Use of Technology (UTAUT2) was extended to determine the factors affecting the acceptance of eLearning platforms for medical education in the Philippines during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eLearning has been the medium of delivery of medical educational institutions to address the scarcity of medical professionals [ 30 , 31 , 32 ]. In this study, the Unified Theory of Acceptance and Use of Technology (UTAUT2) was extended to determine the factors affecting the acceptance of eLearning platforms for medical education in the Philippines during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, eLearning has been widely utilized as the medium of instruction, including among medical students [ 30 , 31 ]. In this study, the UTAUT2 was extended to determine the factors affecting the acceptance of eLearning platforms (e.g., Moodle, Docebo, and Blackboard [ 39 ]) in medical education in the Philippines during the COVID-19 pandemic [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of national COVID-19 infection-control recommendations, dental faculties had to suspend in-person instruction, and teaching activity was conducted online. Some researchers who focused on online dental education pointed out the rapid change adopted by dental faculties in many countries, such as the USA [ 6 , 7 , 8 , 9 ], Germany [ 10 ], Italy [ 11 ], China [ 12 , 13 ], Chile [ 14 ], Brazil [ 8 , 15 , 16 ], Pakistan [ 17 ], Nepal [ 18 , 19 ], Indonesia [ 20 ], India [ 21 , 22 ], Jordan [ 23 ], Romania [ 24 , 25 , 26 ], Portugal [ 27 , 28 ], Cyprus [ 29 ], Australia [ 8 , 30 ], and Spain [ 31 ]. During the first year of the pandemic, the academic research teams additionally wanted to identify the differences between countries in what aspects of dental education were disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have utilized software log data, questionnaires, interviews, and more [3,4,6,7]. Though these data sources are beneficial for understanding our studied phenomenon, we add a new perspective by analyzing students' naturally occurring reflections.…”
Section: Methodsmentioning
confidence: 99%
“…Students have reported several challenges and low satisfaction with engaging in virtual learning during COVID-19 [1,4]. In contrast, other authors have reported that health professions students have adapted well from the challenges and virtual learning has resulted in better attendance, engagement, and feedback as both teaching staff and students have created various ways to cope [5,6].…”
Section: Introductionmentioning
confidence: 99%